Identification of cardioprotective miRNAs (protectomiRs) in a porcine model of acute myocardial infarction and cardioprotection by ischemic conditioning. (10th June 2022) - Nagy, RN; Makkos, A; Baranyai, T; Giricz, Z; Kiss, B; Puskas, LG; Farago, N; Lukovic, D; Gyongyosi, M; Gorbe, A; Ferdinandy, P
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): National Research, Development and Innovation Office of Hungary (NKFIA; NVKP-16-1-2016-0017 National Heart Program and OTKA-FK 134751) MTA-SE System Pharmacology Research Group, Department of Pharmacology and Pharmacotherapy, Semmelweis University, H-1089 Budapest, Hungary Introduction: Changes in the expression profile of microRNAs contribute to cardioprotective signaling. We have previously identified cardioprotective microRNAs, termed protectomiRs, by a systematic analysis of microRNA expression pattern in myocardial infarction and cardioprotection induced by ischemic conditioning in rats. ProtectomiRs may be important therapeutics for cardioprotection. Purpose: We aimed to identify protectomiRs in a translational porcine model of reperfused acute myocardial infarction (AMI) and cardioprotection, and validate their cardiocytoprotective effect. Methods: We used cardiac tissue samples from our previous study in closed-chest AMI model in domestic pigs. Pigs were subjected to sham operation (Sham), ischemia/reperfusion to induce AMI (AMI) or preconditioning (IPreC), postconditioning (IPostC), and remote perconditioning (RIPerC). Tissue samples were collected from the infarcted region of the left ventricles. MiRNA expression pattern was detected by high-throughput qRT-PCR. Potential protectomiRs were selected by systematic comparison of significant expression changes due to different conditioning stimuli vs. AMI. To validate the cardiocytoprotective effect of potential protectomiRs, isolated rat cardiomyocytes were transfected with specific miRNA mimics or inhibitors (antagomiRs) of the selected protectomiRs, and the survival of cells was measured after simulated ischemia/reperfusion injury. Results: Expression of 221 miRNAs was assessed. Expression of 57 microRNAs were changed by IPreC, 54 by IPostC and 68 by RIPerC as compared to AMI (min. 1, 5×log2 fold-change, -log10p>1, 31 vs. AMI). Expression of 14 microRNAs changed significantly due to all three conditionings vs. AMI (10 miRNAs were downregulated and 4 upregulated). Rat homologs of these 14 protectomiR candidates were identified and 13 showed 100% sequence homology with the original pig miRNAs. The selected miRNAs (9 antagomiRs and 4 miRNA mimics) were transfected in isolated rat cardiomyocytes. Modulation of 2 mimics of these miRNAs significantly improved the survival of cells after ischemia/reperfusion injury (due to intellectual property protection, we do not disclose the protectomiRs here). Conclusion: Here we identified 2 miRNAs in a clinically relevant porcine model of AMI that can be potential therapeutic protectomiRs.